The Specific Role of Educational and Pedagogical Mechanisms in the Training of Reserve Officers - Uralov Khusan Bobokulovich (Euro Asian Journal Publishing, 2025)
This article discusses the unique role of educational and pedagogical mechanisms in the training of reserve officers.
Keywords: Education; education; science; professional training